Preliminary Validation on the Factors Influence Political Belief of Flood Victims in Malaysia - Noor Hadzlida Ayob; Mohd Fo’ad Sakdan (International Review of Management and Marketing, 2016)
This study attempt to explore the factors determined the political belief among the flood victims in Malaysia. In disaster situation such as flood, political institution plays a significant role in supplying aid for the victims. However, even with the same relief assistant that had been provided by the government, different appraisals often heard from the victims. Criticizes and compliments regarding the ways of the political institution handling the aid are among the issues that have been highlighted. These different perspectives of views represent the different ideological thought and belief system that hold by the victims regarding on ‘how the political institution should be performed in disaster situation’. Hence, relating to the issue, it seems important to understand the prior factors that developing the political belief among the flood victims, before the belief system is formed in the community. In order to understand the political belief, survey towards 759 respondents among the flood victims were executed. The result from the exploratory factor analysis shown that the Political Belief Scale (PBS) that has been developed in this study exhibited an adequate internal reliability, produces good convergent validity in measuring similar factors and performed good discriminant validity with the dissimilar factors. The findings show that the political knowledge is the dominance factor that influences the political belief of flood victims in Malaysia. The implication of this findings was discussed.